The importance of place : explaining the characteristics underpinning the Brexit vote across different parts of the UK /: explaining the characteristics underpinning the Brexit vote across different parts of the UK. (July 2016) - (Research analyst), Clarke, Stephen; Whittaker, Matthew
No abstract available